An Overview of Enhancing the Efficiency of Vapor Compression Cooling Systems by the Implementation of Evaporative Condensers - Hussain, Haider Mumtaz; Hammdi, Salman Hashim (Basrah Journal for Engineering Sciences, 2024)
This paper explores the significance of energy conservation in the context of rising energy consumption and its impact on economic growth. With a focus on cooling systems, particularly evaporative condenser technology, the study aims to investigate its fundamentals, operating principles, and theoretical aspects. The paper delves into the various types of condensers used in cooling systems, emphasizing the role of evaporative condensers in enhancing heat transfer efficiency. The operating principles of evaporative condensers are detailed, considering factors such as air and water flow rates, wet bulb temperatures, and heat transfer coefficients. Theoretical models and mathematical approaches for evaluating evaporative condenser performance are also reviewed. The research includes an extensive review of existing literature on evaporative condenser technology, covering refrigeration models, HVAC systems, and various experimental studies. Theoretical models are discussed, highlighting the challenges in accurately modeling evaporative condenser behavior. The paper also presents achievements and advancements in research, including experiments that demonstrate the positive impact of evaporative cooling on air-cooled condenser systems. Various case studies and experimental validations showcase the potential energy savings and improved performance achieved through the incorporation of evaporative condensers in cooling systems. By switching from an air-cooled to an evaporatively-cooled condenser, one can reduce electricity consumption by 58%, according to research. This alternate condenser type improves performance by 113.4% at from 3 to 3000 kW of cooling power.